Pelatihan Pengelolaan Strategi Bisnis, Manajemen Organisasi dan Keterampilan Usaha bagi Masyarakat Kampung Nanas di Palangka Raya: Business Strategy Management, Organizational Management and Business Skills Training for Kampung Nanas Community in Palangka Raya - Permatasari, Silvani; Malinda, Okta; Idsan, Rakha Satya; Ramadhani, Ahmad; Seiya, Saint (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This service is carried out to help empower the community in relation to taking advantage of business opportunities or entrepreneurship. The target audience taking part in this activity is the Kampung Nanas farming business group on Jalan Kampung Nanas, G.Obos Outer Ring, Kereng Bangkirai Village, Palangka Raya. The reason for carrying out this activity is the lack of understanding regarding the management of business enterprises and group organizations which results in minimal income because it only comes from pineapple sales. Community empowerment is carried out through providing an understanding of managing business strategies in entrepreneurship to increase residents' income and also about how to manage organizational management for farming business groups within it. The counseling delivery methods used are lectures and practice, where practice is carried out through guidance and mentoring. The things explained in the lecture are materials related to entrepreneurial business strategies and organizational or group management, while practice is carried out by providing practical examples of making innovative products from pineapple processed which can be used as another source of income such as nata de leri. There is an increase in partners' knowledge about business strategy through innovation and organizational management which can be seen from the increase in understanding through the posttest.